Controller Parameter Optimization For An Electro-Hydraulic Actuator System Based On Particle Swarm Optimization Technique - Rozaimi, Ghazali (Penerbit Universiti Teknologi Malaysia, 2016)
Motion control applications are widely applied in the industrial field with the assistance of electro-hydraulic actuator (EHA)system.EHA system is well known to be disclosed to the parameter variations,disturbances and uncertainties which are affected by the changes in the operating conditions such as friction,internal and external leakage.The complexity and nonlinear characteristic of the EHA system leads to a great challenge for controller development and system modelling.The performance of the utilized controller can be improved in order to achieve its best capability.In this paper,the basic knowledge in optimization of the proportional-integral-derivative (PID) controller through Gradient Descent (GD) and Particle Swarm Optimization (PSO)techniques are discussed.The PID parameters obtained through Ziegler-Nichols (ZN) tuning method has been optimized by using the GD method and is compared with PSO optimization technique via MATLAB/Simulink software.The findings show significant improvement in positioning tracking performance when the developed optimization technique is applied.Therefore,the issues degrading the EHA system performance have been reduced.